EVALUASI PELATIHAN JARAK JAUH MODEL KIRKPATRICK: STUDI KASUS PJJ COMMUNICATION SKILLS ANGKATAN II PADA BALAI DIKLAT KEUANGAN YOGYAKARTA - Jamila Lestyowati; Ilvi Rahmi (Jurnal Transformasi Administrasi, 2021)
Communication has an important role in supporting task implementation and performance achievement. Human Resources (HR) as an important asset of an organization are required to have communication competencies. At the Ministry of Finance, communication is one of the managerial competencies that employees must possess. To improve communication competence, Communication Skills Training was held. This paper aims to evaluate the Communication Skills Training at the Yogyakarta Financial Education and Training Agency. The evaluation method used is the Kirkpatrick level 1 and 2 methods to measure participant satisfaction with the instructor and administrator, as well as to measure changes in the competence of trainees before and after training. This research is a type of evaluation research using primary and secondary data sources. Primary data comes from questionnaires, test results, and observations, and secondary data comes from document searches. The analysis method uses IPA (Importance Performance Analysis) analysis and paired t test. The results showed that the participants were satisfied and rated the teaching and administration very well with a score of 4.70 for the evaluation of the administration and 4.81 for the evaluation of the trainer. Meanwhile, the participant evaluation shows that there is an increase in the knowledge of the training participants before and after the training.